Corporate Social Responsibility and Company-Community Relations: Evidence from Newmont Ghana Gold Limited in Asutifi North District, Ghana - Arthur, Dominic Degraft; Opoku, Felix Kwame; Issifu, Abdul Karim (EBSU Journal of Social Sciences and Humanities, 2021)
The purpose of this study was to investigate the effects of NGGL’s corporate social responsibility activities on a peaceful relation with communities in their operational areas. Data were collected using the in-depth interview, focus group discussion and observation. The purposive sampling technique was used to select fifty (50) community respondents and twenty (20) key informants for the study. In sum, there were seventy (70) respondents selected for the study. An analysis of the data collected showed that the NGGL’s CSR has significantly contributed to the growth and development of the Asutifi North District, thereby compelling the inhabitants to respond positively, each time the company calls on them. Following these findings, it was recommended that stakeholders and government agencies should work together to design a policy on CSR, such that every sector of the economy contributes to providing total socio-economic responsibilities to improve development of Ghana.